Bone evaluation in paediatric chronic kidney disease: clinical practice points from the European Society for Paediatric Nephrology CKD-MBD and Dialysis working groups and CKD-MBD working group of the ERA-EDTA - Bakkaloğlu, Sevcan A.; Bacchetta, Justine; Lalayiannis, Alexander D.; Leifheit-Nestler, Maren; Stabouli, Stella; Haarhaus, Mathias; Reusz, George; Groothoff, Jaap; Schmitt, Claus P.; Evenepoel, Pieter; Shroff, Rukshana; Haffner, Dieter (Nephrology, dialysis, transplantation, 2021)
Abstract. Mineral and bone disorder (MBD) is widely prevalent in children with chronic kidney disease (CKD) and is associated with significant morbidity. CKD ma
Advance access publication 2 November 2020
Gesehen am 12.07.2021